Comparative outcomes of SARS-CoV-2 primary and reinfection in older adult patients - Tey, Shu-Farn; Tsai, Ya-Wen; Wu, Jheng-Yan; Liu, Ting-Hui; Chuang, Min-Hsiang; Hsu, Wan-Hsuan; Huang, Po-Yu; Lai, Chih-Cheng; Hsu, Chi-Kuei (Frontiers in Public Health, 2024)
Background The outcomes of older adult people acquiring SARS-CoV-2 reinfection was unclear. This study aimed to compare the outcomes of older adult patients with COVID-19 reinfection and those with primary infection. Methods This retrospective cohort study used electronic medical records from the TriNetX Research Network. Older adult patients (aged ≥65 years) with COVID-19 between January 1, 2022, and December 31, 2022, were included in the study. The patients were subsequently categorized into reinfection or primary infection groups, according to whether they manifested two distinct COVID-19 episodes with an intervening period of more than 90 days. Propensity score matching was performed for covariate adjustment between the reinfection and primary infection groups. The primary outcome was a composite outcome, including emergency department visits, hospitalization, intensive care unit admission, mechanical ventilation use, and mortality, following primary infection and reinfection. Results After matching, 31,899 patients were identified in both the reinfection and primary infection groups. The risk of primary composite outcomes was 7.15% (n = 2,281) in the reinfection group and 7.53% (n = 2,403) in the primary infection group. No significant difference in the primary outcome was observed between groups (HR, 0.96; 95% CI, 0.91 to 1.02, p = 0.17). In addition, there was no significant differences between the reinfection and primary infection groups in terms of emergency department visit (HR, 1.03; 95% CI, 0.95 to 1.11, p = 0.49), all-cause hospitalization (HR, 0.94; 95% CI, 0.86 to 1.02, p = 0.14), intensive care unit admission (HR, 0.92; 95% CI, 0.67 to 1.28, p = 0.62), mechanical ventilation use (HR,1.35 95% CI, 0.69 to 2.64 p = 0.38), and all-cause mortality (HR, 0.94; 95% CI, 0.74 to 1.20, p = 0.62). Conclusion There were no significant differences in clinical outcomes between older adult patients with COVID-19 reinfection and those with primary infection.